2021
DOI: 10.3390/met11050718
|View full text |Cite
|
Sign up to set email alerts
|

The Advancement of 7XXX Series Aluminum Alloys for Aircraft Structures: A Review

Abstract: 7XXX series aluminum alloys (Al 7XXX alloys) are widely used in bearing components, such as aircraft frame, spars and stringers, for their high specific strength, high specific stiffness, high toughness, excellent processing, and welding performance. Therefore, Al 7XXX alloys are the most important structural materials in aviation. In this present review, the development tendency and the main applications of Al 7XXX alloys for aircraft structures are introduced, and the existing problems are simply discussed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
74
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(80 citation statements)
references
References 125 publications
0
74
0
6
Order By: Relevance
“…7XXX series Al alloy possesses intrinsic properties such as high strength-to-density ratio, high-specific stiffness, and toughness characteristics making it an ideal candidate material for structural parts in automotive and aerospace applications [16,17]. The addition of reinforcement (organic, inorganic, industrial and agriculture waste, carbides, nitrides, oxides, CNTs, compounds) to aluminium matrix resulted in multiphase materials (composite materials) which improve the specific properties and attract engineering applications [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…7XXX series Al alloy possesses intrinsic properties such as high strength-to-density ratio, high-specific stiffness, and toughness characteristics making it an ideal candidate material for structural parts in automotive and aerospace applications [16,17]. The addition of reinforcement (organic, inorganic, industrial and agriculture waste, carbides, nitrides, oxides, CNTs, compounds) to aluminium matrix resulted in multiphase materials (composite materials) which improve the specific properties and attract engineering applications [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The above literature review confirms that limited studies have been carried out with industrial wastes as potential reinforcement materials for fabricating composites, although reinforcement particles offer beneficial properties. Al 7XXX series alloys are ultra-high-strength materials and therefore 70% of materials are used for structural applications in aircraft [16,50]. It was observed that 60% of structural parts are fabricated viz.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The applications of PCD cutting materials are mainly in turning all pure nonferrous metals and nonferrous materials with little or no abrasive filler content [9]. Among the most commonly used nonferrous materials are aluminum alloys, which are used not only in mechanical engineering but also in many other industries [10].…”
Section: Introductionmentioning
confidence: 99%